Franchising Telecom Service Shops : Meeting Demand from Nonsubscribers in Indonesia - Pradhan, Rajesh; Smith, Peter (World Bank, Washington, DC, 2012)
Indonesia has only about 1.3 lines per hundred people, so universal telephone service cannot be practically achieved in the near future. Nevertheless, public access to telephone and other telecommunications services can be dramatically improved through pay phones and telecom shops. The telecom shops are retail outlets that provide telecom services to "non-subscribers," often under a franchise from the local telephone company. These shops have turned out to be effective at meeting the strong demand among the majority of Indonesians who lack private residential or business telephone service, and their success provides a model that other countries can apply. The important message from the Indonesian experience is that the demand for service from nonsubscribers in developing countries is significant, commercially viable, and should be met. The rapid growth in the number of telecom shops in Indonesia attests to their increasingly effective role in providing public access to telecommunications services. As technology advances and the cost of telecommunications equipment declines, the next commercial development could be the establishment of community "micro" telephone companies. Using a small PBX (an automatic switchboard), a telecom shop could cost-effectively service one hundred extensions on twenty main lines and, using the new generation of digital cordless telephone sets, the telecom shop could extend its services while still providing conventional telecommunications shop services.